Prevalence and determinants of cardiovascular disease risk factors using the WHO STEPS approach in Cochabamba, Bolivia - Yercin Mamani-Ortiz; Miguel San Sebastián; Ada X. Armaza; Jenny M. Luizaga; Daniel E. Illanes; Marcia Ferrel; Paola A. Mosquera (BMC, 2019)
Abstract Background Cardiovascular diseases (CVDs) are considered the number one cause of death worldwide, especially in low- and middle-income countries, Bolivia included. Lack of reliable estimates of risk factor distribution can lead to delay in implementation of evidence-based interventions. However, little is known about the prevalence of risk factors in the country. The aim of this study was to assess the prevalence of preventable risk factors associated with CVDs and to identify the demographic and socioeconomic factors associated with them in Cochabamba, Bolivia. Methods A cross-sectional community-based study was conducted among youth and adults (N = 10,704) with permanent residence in Cochabamba, selected through a multistage sampling technique, from July 2015 to November 2016. An adapted version of the WHO STEPS survey was used to collect information. The prevalence of relevant behavioural risk factors and anthropometric measures were obtained. The socio-demographic variables included were age, ethnicity, level of education, occupation, place of residence, and marital status. Proportions with 95% confidence intervals were first calculated, and prevalence ratios were estimated for each CVD risk factor, both with crude and adjusted models. Results More than half (57.38%) were women, and the mean age was 37.89 ± 18 years. The prevalence of behavioural risk factors were: current smoking, 11.6%; current alcohol consumption, 42.76%; low consumption of fruits and vegetables, 76.73%; and low level of physical activity, 64.77%. The prevalence of overweight was 35.84%; obesity, 20.49%; waist risk or abdominal obesity, 54.13%; and raised blood pressure, 17.5%. Indigenous populations and those living in the Andean region showed in general a lower prevalence of most of the risk factors evaluated. Conclusion We provide the first CVD risk factor profile of people living in Cochabamba, Bolivia, using a standardized methodology. Overall, findings suggest that the prevalence of CVD risk factors in Cochabamba is high. This result highlights the need for interventions to improve early diagnosis, monitoring, management, and especially prevention of these risk factors.